Pembelajaran Daring Dimasa Pandemi Covid-19 pada Mata Pelajaran Estimasi Biaya Konstruksi di SMK Negeri 1 Batumandi Kalimantan Selatan - Kartika Tri Buana; Sutarto Sutarto (Universitas Negeri Yogyakarta, 2022)
ABSTRACTThe purpose of this study was to determine the responses of students about online learning in the subject of Construction Cost Estimation at SMKN 1 Batumandi. In detail, the purpose of this study is to find out (1) the variation of online learning tools used, (2) the supporting and inhibiting factors in online learning, (3) the level of mastery of students about the use of technological tools, (4) the motivation of students in online learning. , (5) the independence of students in online learning, and (6) the accuracy of students in online learning. This research is descriptive research with a quantitative approach. The research was conducted at SMK Negeri 1 Batumandi, South Kalimantan. The subjects in this study were all 15 students of class XII of the Building Modeling and Information Design (DPIB) skill program. Data collection techniques using a questionnaire. The data analysis technique used in this research is descriptive quantitative. The results showed: (1) all students (100%) used smartphones, the most students (87%) used data packets for internet network access, and the most students (87%) sourced costs for network access came from people elder/guardian. (2) The results of the supporting factors, students (53.3%) stated that online media was always easy to use, the level of expertise of students using online media was at the level of quite expert as much as 60%. The results of the inhibiting factors, students (40%) stated that the internet network for access was not supported, students (60%) experienced internet network barriers, students (45%) experienced less stable internet networks, and students (45,7%) no minor health problems. (3) Students' mastery of technological tools is included in the high category with 6 students. (4) The motivation of students is in the very high category with 8 students. (5) The independence of students is in the very low category with 6 students. (6) The accuracy of students is in the very high category with 5 students.Keywords: Online Learning, Online Media, Contruction Cost EstimationABSTRAKTujuan penelitian ini untuk mengetahui tanggapan peserta didik tentang pembelajaran online pada mata pelajaran Estimasi Biaya Konstruksi di SMKN 1 Batumandi. Secara rinci tujuan penelitian ini adalah untuk mengetahui (1) variasi perangkat pembelajaran daring yang digunakan, (2) faktor pendukung dan penghambat dalam pembelajaran daring, (3) tingkat penguasaan peserta didik tentang penggunaan alat teknologi, (4) motivasi peserta didik dalam pembelajaran daring, (5) kemandirian peserta didik dalam pembelajaran daring, dan (6) kecermatan peserta didik dalam pembelajaran daring. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Penelitian dilakukan di SMK Negeri 1 Batumandi, Kalimantan Selatan. Subjek pada penelitian ini adalah seluruh peserta didik kelas XII program keahlian Desain Pemodelan dan Informasi Bangunan (DPIB) yang berjumlah 15 orang. Teknik pengumpulan data menggunakan angket. Teknik analisis data yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Hasil penelitian menunjukkan: (1) seluruh peserta didik (100%) menggunakan smartphone, peserta didik paling banyak (87%) menggunakan paket data untuk akses jaringan internet, dan peserta didik paling banyak (87%) sumber biaya untuk akses jaringan berasal dari orang tua/wali. (2) Hasil faktor pendukung, peserta didik (53,3%) menyatakan media online selalu mudah digunakan, tingkat keahlian peserta didik menggunakan media online berada ditingkat cukup ahli sebanyak 60%. Hasil faktor penghambat, peserta didik (40%) menyatakan jaringan internet untuk akses tidak mendukung, peserta didik (60%) mengalami hambatan jaringan internet, peserta didik (45%) mengalami jaringan internet kurang stabil, dan peserta didik (45,7%) tidak mengalami gangguan kesehatan ringan. (3) Penguasaan peserta didik tentang alat teknologi termasuk dalam kategori tinggi dengan 6 peserta didik. (4) Motivasi peserta didik masuk dalam kategori sangat tinggi dengan 8 orang peserta didik. (5) Kemandirian peserta didik masuk dalam kategori sangat rendah dengan 6 orang peserta didik. (6) Kecermatan peserta didik masuk dalam kategori sangat tinggi dengan 5 peserta didik.